A demand‐based spectrum orthogonalisation scheme for interference avoidance in LTE‐Advanced heterogeneous networks. Issue 10 (11th August 2014) - Mohamad Maharum, Siti M.; Fisal, Norsheila; Lo, Anthony; Ghafar, Aimi S. A.; Saparudin, Faiz Asraf; Katiran, Norshidah
Abstract: Successful deployment of femtocells within a macrocell coverage area would be hindered if cross‐layer and co‐layer interference in such heterogeneous networks (HetNets) is not properly mitigated. Through spectrum management, cross‐layer interference between macrocell and femtocell network layers can be avoided by assigning the network layers with orthogonal spectrum bands. However, the orthogonal spectrum assignments in prior works are no longer effective because they may not guarantee the variation of users' traffic demand in HetNets to be satisfied all the time. Therefore, a centralised and dynamic orthogonal spectrum assignment called demand‐based spectrum orthogonalisation (DeBaSO) is proposed in this paper to address the interference issues in downlink of LTE‐Advanced HetNets. In our proposed scheme, the problem of orthogonal spectrum assignment is formulated with the objective to maximise the overall system throughput based on the requirement of physical spectral resources to satisfy the users' traffic demand. Additionally, the co‐layer interference among femtocells is avoided by grouping the adjacent femtocells into different femtocell clusters. To do so, typical model of spatial frequency reuse is exploited in this paper. In this way, femtocells that are grouped within the same cluster can universally reuse the assigned spectrum resource without creating co‐layer interference among them. Numerical results indicate that the proposed scheme achieves a remarkable performance in terms of overall system throughput and spectrum efficiency because the cross‐layer and co‐layer interference is entirely avoided. The achievements prove that DeBaSO scheme overcomes the limitations found in other orthogonal spectrum assignments, which were previously proposed in the literature. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : A centralised and dynamic orthogonal spectrum assignment scheme is proposed to address cross‐layer and co‐layer interference when deploying closed‐access mode femtocells within a macrocell site. Simulation results show that when compared with other spectrum assignments in the literature, the proposed scheme performs remarkably in terms of system throughput and spectrum efficiency because the interference is avoided. The proposed scheme manages to support the entire UEs' transmission in both macrocell and femtocell network layers at the expense of full spectrum utilisation.